Innovations In Molecular Diagnostics: Advancements And Challenges In Clinical Laboratories (Journal of Namibian Studies : History Politics Culture, 2024)
Molecular diagnostics has rapidly transformed clinical laboratories, offering precise and targeted analysis of genetic material, which is crucial for personalized medicine, oncology, and infectious disease management. This paper explores key advancements in molecular diagnostics, including next-generation sequencing (NGS), digital PCR (dPCR), CRISPR-based diagnostics, and microarray technology. These innovations have significantly enhanced diagnostic accuracy, efficiency, and the ability to detect low-abundance targets. However, their integration into clinical practice presents several challenges, including the need for specialized equipment and expertise, high costs, and ethical and regulatory complexities. Additionally, managing and interpreting the vast amounts of data generated by these technologies remains a significant hurdle. The paper discusses these advancements and challenges, highlighting the future directions of molecular diagnostics, including the potential of emerging technologies and the importance of standardization and collaboration across disciplines. Addressing these challenges will be essential for realizing the full potential of molecular diagnostics in improving patient care.